1996
DOI: 10.1073/pnas.93.10.4957
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of epidermal growth factor in conscious rats and monkeys.

Abstract: The therapeutic application of growth factors to human disease has become closer to reality with the advent of faster means of synthesizing these molecules and novel drug delivery strategies. Epidermal growth factor (EGF) belongs to a large family of molecules with the ability to modulate growth. Purified extracts of EGF have been used clinically to modulate gastrointestinal secretion of hormones and accelerate healing. EGF is also reported to have both vascular smooth muscle contractile and relaxing activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…VEGF preferentially dilates arterioles and venules without an effect on medium-sized arteries and veins [18]. Subsequently, several studies in humans and animals have demonstrated a hypotensive effect of a variety of AGF (Table 1 [19][20][21][22][23][24][25][26][27]). In the VIVA (VEGF in Ischemia for Vascular Angiogenesis) trial, both intracoronary and intravenous infusions of recombinant human VEGF produced falls in systolic blood pressure of up to 22% at the highest doses [19].…”
Section: Vasomotor Effects Of Angiogenic Growth Factors and Their Recmentioning
confidence: 98%
“…VEGF preferentially dilates arterioles and venules without an effect on medium-sized arteries and veins [18]. Subsequently, several studies in humans and animals have demonstrated a hypotensive effect of a variety of AGF (Table 1 [19][20][21][22][23][24][25][26][27]). In the VIVA (VEGF in Ischemia for Vascular Angiogenesis) trial, both intracoronary and intravenous infusions of recombinant human VEGF produced falls in systolic blood pressure of up to 22% at the highest doses [19].…”
Section: Vasomotor Effects Of Angiogenic Growth Factors and Their Recmentioning
confidence: 98%
“…Beside these renal effects, a prolonged decrease in blood pressure found in conscious rats treated subchronically with EGF (Keiser and Ryan, 1996) could contribute to the fall in GFR. In contrast to the latter paper, reporting an increase in kidney weight after 4 weeks pretreatment with EGF, in our study the kidney weight was reduced, but only to a slight degree.…”
Section: Discussionmentioning
confidence: 94%
“…In some studies vasodilating and/or blood pressure-lowering effects of EGF have been reported [46,47], whereas in others no effect or increase in blood pressure after EGF administration have been observed [48,49]. Moreover, ERK and PI3-K have also been implicated in vasoconstrictor response.…”
Section: Egfr and Vascular Tonementioning
confidence: 99%